Mediating role of psychological well-being in the effect of spirituality on attitudes toward death in the elderly - Sarpdaği, Yakup; Yiğit, Muhammet Faruk; Aydin, Muhammet Ali; Yildirim, Mehmet Salih; Çiftci, Necmettin; Yildiz, Metin (John Wiley and Sons Inc, 2025)
Background: Spirituality and psychological well-being are important in shaping attitudes toward death. Objective: This study was conducted to determine the mediating role of psychological well-being in the effect of spirituality on attitudes toward death in the elderly. Method: This cross-sectional descriptive study was conducted in a province of Turkey between February 2024 and June 2024 with 467 individuals aged 65 years and older. The variables affecting attitudes toward death were identified by conducting mediation analysis and predictive analysis with a machine learning approach. Data were analyzed using SPSS 22.0, G*Power 3.1, R programming language 4.1.3 programs. Results: In our study, the effect of spirituality on psychological well-being was found to be positive and statistically significant (coefficient = 0.660, P < 0.001). The direct effect of spirituality on neutrality and approaching acceptance, sub-dimensions of attitude toward death, was significant (coefficient = 1.603, P < 0.001), and its indirect effect through psychological well-being was also significant (coefficient = 0.179, lower limit confidence interval (LLCI) = 0.085, upper limit CI (ULCI) = 0.309). The direct effect of spirituality on escape acceptance (coefficient = 0.571, P < 0.001), one of the attitudes toward death sub-dimensions, was significant, but the mediation effect of psychological well-being was not significant (LLCI = −0.049, ULCI = 0.0438). The direct effect of spirituality on fear and avoidance of death, one of the attitudes toward death sub-dimensions, was not statistically significant at the 95% confidence level (coefficient = 0.094, P = 0.433). The indirect effect of psychological well-being on fear and avoidance of death was negative and significant (coefficient = −0.136, LLCI = −0.233, ULCI = −0.031). Conclusion: In this study, as spirituality increases, attitudes toward death also increase positively. It was found that as spirituality increases, people tend to have a more positive acceptance and approach toward death. This study suggests that spirituality may influence emotional responses to death and shape attitudes toward death, particularly neutral acceptance and escape acceptance. As psychological well-being increases in the elderly, acceptance of death increases and fear of death decreases. In the study, prediction with different machine learning approaches is proposed. Longitudinal studies on attitudes toward death are recommended. © 2025 Japanese Psychogeriatric Society.
Keywords: death; elderly; psychological well-being; spirituality